The Role of Customer Perceived Value Mediates the Effect of Service Quality on Customer Satisfaction - Ni Made Purnami; A.A Ngr Wishrawan Bhaskara Warman (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the quality of service to customer satisfaction through the perceived value in Sing Ken Ken Lifestyle Boutique Hotel. This study used 130 respondents through purposive sampling method. Data collection methods used through questionnaires. Data analysis technique which is technique of path analysis and test of sobel. The results showed that the service quality is positive and significant on the perceived value of the customer, the service quality is positive and significant on customer satisfaction, the perceived value of the customer, and the perceived value of consumers as mediation of service quality to customer satisfaction. The results showed that the service quality and customers perceived value can affect consumer satisfaction and the perceived value consumers can mediate the effect of service quality to customer satisfaction.